Governance and moderating effects of environmental uncertainty: The impact on performance in horizontal logistics cooperations - Ralf Elbert; Ulf-Thido Gerdes; Gernot Kaiser; Tessa Sarnow (Logistics Research, 2018)
Governance mechanisms are viewed as critical to prevent opportunism in horizontal cooperations, as they are more conflicting in nature than vertical cooperations. Although these forms of cooperations become particularly popular under uncertain conditions, they have not yet been analyzed in depth with respect to the efficiency of governance mechanisms under those uncertain external conditions. In this paper, we therefore seek to extend the stream of research on logistics research by systematically investigating the impact of perceived environmental uncertainty on the effectiveness of governance mechanisms in horizontal cooperations. Specifically, the paper examines relational and transactional mechanisms of governance. We collected data from 181 logistics service providers (LSPs) operating in Africa and the Middle East and analyzed the moderating effect of uncertainty on governance mechanisms using the partial least squares method. Our results suggest that relational, as well as transactional governance mechanisms, alone are not sufficient to prevent opportunism if the environmental conditions are stable. However, if the environment surrounding these cooperations is uncertain, transactional, as well as relational forms of governance become efficient governance mechanisms. To facilitate further the interpretation of the findings from our survey analysis, in-depth interviews were conducted with selected companies from our sample.
Keywords: 650; horizontal cooperations; environmental uncertainty; logistics service providers; emerging economies